2013
DOI: 10.1016/j.ins.2013.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Lossy-to-lossless 3D image coding through prior coefficient lookup tables

Abstract: Abstract-This paper describes a low-complexity, highefficiency, lossy-to-lossless 3D image coding system. The proposed system is based on a novel probability model for the symbols that are emitted by bitplane coding engines. This probability model uses partially reconstructed coefficients from previous components together with a mathematical framework that captures the statistical behavior of the image. An important aspect of this mathematical framework is its generality, which makes the proposed scheme suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…These image types belong to different fields and are captured with different sensors. As observed in other works [16], [17], [33], the data produced after transforming images of the same type with the same wavelet filter-bank are statistically similar. We exploit this fact to generate a single lookup table (LUT) for each image type.…”
Section: A Main Insightssupporting
confidence: 82%
“…These image types belong to different fields and are captured with different sensors. As observed in other works [16], [17], [33], the data produced after transforming images of the same type with the same wavelet filter-bank are statistically similar. We exploit this fact to generate a single lookup table (LUT) for each image type.…”
Section: A Main Insightssupporting
confidence: 82%
“…The LUT is different for each image type since the probability model exploits the fact that the data produced after transforming images of the same type (e.g., natural, medical, etc.) with the same wavelet filter-bank are statistically similar [35], [37], [38]. A more in-depth study on this stationary probability model can be found in [33].…”
Section: B Context Formation and Probability Modelmentioning
confidence: 73%
“…Recently, a probability model that avoids the use of adaptive mechanisms has been introduced in [14], [15]. Its main idea is that the probability of the symbols can be estimated depending on the bitplane and the context in which they are emitted.…”
Section: B Image Coding With Jpeg2000mentioning
confidence: 99%